Naasteliefde as uitdaging aan die Afrikaner - I. W. C. van Wyk (In die Skriflig, 1998)
Afrikaners and their churches were accused of lovelessness during the apartheid years. The time has come for us not only to reflect on the commandments to love, but also to obey these commandments in our lives. The essence of neighbourly love is therefore highlighted in this article and Afrikaners are called upon to practise this love in Africa and South Africa where we live - no matter how difficult it may be.